THE TIMING OF UNAVOIDABLY SPOILED UNITS. - Newlove, G. H. (The Accounting Review, 1960)
Abstract In this article the author explains, illustrates and compares the mathematical computations and resulting valuations of three primary methods of accounting for unavoidably spoiled units in process cost industries. According to the first method, spoiled units are assumed to be taken out of production at the start of operations. In second method, spoiled units are assumed to be discovered by inspection after they are completely processed. In the third method, spoiled units are taken out of production when spoiled and loss on spoiled and loss on spoilage treated as overhead of the department in which the spoilage occured. Under the first method, the spoiled units are weighted by zero and loss on spoilage is allocated beteen the units completed and the units still in process on the basis of the equivalent production. Under the second method, the spoiled units are weighted by unity and the units remaining in process are costed as though there were no spoiled units thereby making the good completed units absorb all spoilage loss.